On the Menelaus and Ceva 6-Figures in the Fibered Projective Planes - Ayşe Bayar; Süheyla Ekmekçi (Abstract and Applied Analysis)
The fibered versions of Menelaus and Ceva 6-figures in the fibered projective plane are given and the conditions to the fibered versions of Menelaus and Ceva 6-figures in the fibered projective plane with base plane, that is, projective plane, are determined.